Engineering cyanide-tolerant Arabidopsis thaliana - Molojwane, Emang Tsametse Emi (Department of Molecular and Cell Biology, 2016)
Cyanide is highly toxic as it inhibits respiration in aerobic organisms by binding to cytochrome c oxidase in the mitochondrial electron transport chain. Plants naturally produce cyanide from the hydrolysis of cyanogenic glycosides and as a by-product of ethylene biosynthesis. β-Cyanoalanine synthase prevents self-poisoning by combining endogenous cyanide with cysteine in the mitochondria to form β-cyanoalanine, which is further hydrolysed to asparagine, or aspartate and ammonia, by plant nitrilase 4 enzymes. β-Cyanoalanine synthase activity enables plants to detoxify limited concentrations of exogenous cyanide. However, phytotoxicity and death occur from exposure to relatively low concentrations of exogenous cyanide. In contrast, some microorganisms have a high capacity for cyanide detoxification due to a number of metabolic pathways including the degradation of cyanide to formate and ammonia; or formamide, by bacterial cyanidase (CynD) and fungal cyanide hydratase (CHT), respectively. Environmental contamination caused by failure to contain cyanide from anthropogenic sources is an important global problem. Hydrometallurgical gold mining utilises cyanide as a lixiviant due to the high affinity of cyanide for gold and the stability of the resulting cyanometallic complexes in aqueous solution, and thus is a significant source of cyanide contamination of soil and water. Biological treatment methods for cyanide, such as phytoremediation, could provide alternatives to the currently used chemical destruction techniques with their associated disadvantages. The use of phytoremediation would require plants to tolerate high concentrations of cyanide in soil. Two attempts have previously been made, with some success, to increase cyanide tolerance in Arabidopsis by genetic engineering: the first, by augmenting the β-cyanoalanine synthase pathway using a microbial nitrilase; and, the second, by introducing a microbial detoxification pathway targeted to the chloroplasts while overexpressing the endogenous enzyme which metabolises the product of the cyanide detoxification reaction. The aim of the current study was to determine whether Arabidopsis thaliana could co-opt the CynD and CHT genes from the cyanide-degrading Bacillus pumilus and Neurospora crassa to detoxify higher levels of cyanide using the encoded enzymes, and whether targeting CynD and CHT to the mitochondria would confer a greater enhancement of cyanide tolerance on plants compared to targeting to the cytoplasm.